Comprehensive Analysis of Differentially Expressed Profiles of mRNA N6-Methyladenosine in Colorectal Cancer - Li, Na; Guo, Qin; Zhang, Qiao; Chen, Bai-Jun; Li, Xiao-An; Zhou, Yan (Frontiers in Cell and Developmental Biology, 2022)
Aim: To comprehensively profile the landscape of the mRNA N6-methyladenosine (m6A) modification in human colorectal cancer (CRC). Methods: Methylated RNA immunoprecipitation sequencing (MeRIP-seq) was explored to compare the difference in mRNA N6-methyladenosine (m6A) methylation between CRC tissues and adjacent normal control (NC) tissue. RNA-sequencing (RNA-seq) was performed to transcribe differentially expressed mRNAs. Conjoint analysis of MeRIP-seq and RNA-seq data was conducted to predict RNA-binding proteins (RBPs). Results: MeRIP-seq identified 1110 differentially m6A methylated sites (DMMSs) and 980 differentially m6A methylated genes (DMMGs) in CRC, with 50.13% of all modified genes showing unique m6A-modified peaks in CRC. RNA-seq showed 915 upregulated genes and 1463 downregulated genes in CRC. QRT-PCR verified the RNA-seq results by detecting the expression of some mRNAs. Conjoint analysis of MeRIP-seq and RNA-seq identified 400 differentially m6A methylated and expressed genes (DEGs), and pathway analysis detected that DMMGs and DEGs were closely related to cancer. After analyzing these DMMGs and DEGs through the GEPIA database, we found that the expression of B3GNT6, DKC1, SRPK1, and RIMKLB were associated with prognosis, and the expression of B3GNT6 and RIMKLB were associated with clinical stage. 17 RBPs were identified based on the DMMGs and DEGs, among which FXR1, FXR2, FMR1, IGF2BP2, IGF2BP3, and SRSF1 were obviously highly expressed in CRC, and FMR1, IGF2BP2, and IGF2BP3 were closely related to methylation, and might be involved in the development of CRC. Conclusion: This study comprehensively profiled m6A modification of mRNAs in CRC, which revealed possible mechanisms of m6A-mediated gene expression regulation.